A Slang Analysis Used in the Movie “Fast Five” - Pramana, I kadek yuda; I Dewa Ayu Devi Maharani Santika (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This research explores the slang words used in the film